Study on entrepreneurial intention in students of the degree in Social Work: Intención emprendedora en estudiantes de Trabajo Social - García-Uceda, Esperanza; Asín, Jesús (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
A study of the determinants of entrepreneurial intention (IE) in university students of the Degree in Social Work at the beginning of their education for entrepreneurship is presented. The data obtained from a sample of students of the subject “Management of Organizations”, included in the 3rd year of the Degree at the University of Zaragoza (Spain). 139 students participated out of 184 enrolled. A logistic regression model was used to analyze the relationship between these factors and the binary variable expressing IE. Significant influence was identified in Responsibility, Creativity and Self-knowledge, with a positive effect.